Evaluation of perinatal factors in neonatal sepsis at tertiary centre - Kumar, Raju; Kumari, Anita; Kumari, Anjili; Verma, Neelam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Neonatal mortality in India continues to remain a major health problem. Neonatal infections are one of the major contributor to neonatal mortality causing approximately one-quarter of the deaths. The signs of neonatal sepsis may be non-specific and easily missed, especially in the early stages. A high index of suspicion and identification of both maternal and neonatal risk factors is an important for early identification and prompt treatment. Methods: This is prospective study done at Patna medical college and hospital Patna from February 2014 to January 2015 in department of paediatrics. All inborn and out born neonates who had clinical signs of sepsis were included in the study. Results: During the 1-year study period, there were a total of 910 admissions in the NICU, out of which 175 were admitted due to neonatal septicaemia. Incidence of neonatal septicaemia was approximately 20%. Mean age at presentation was 4.8±6.38). Low birth weight (60%), preter delivery (60.57%), male gender (66.85%) and low APGAR score at1 minute were common foetal risk factor and prolonged labour (41.14%) and multiple vaginal examination (36.57%), PROM in 28%, MSL (25.71%) were common maternal risk factors. Present study documented a culture positivity rate of 42.28%. E. coli (37.83%) was the most common isolated organism in early as well as LOS. Staphylococcus aureus (20.27%) was the most common isolated Gram-positive bacterium. Mortality rate was 45.14%. Mortality was more in preterm babies (57.54%) which was statically significant p value <0.001. Conclusions: Neonatal septicemia is common and serious condition with high mortality rate. Since the condition starts with vague clinical signs, one has to keep very high index of suspicion to diagnose neonatal sepsis. Diagnosis and treatment at the early stage is very important for favorable outcome. Proper antenatal care, and institutional delivery may decrease neonatal sepsis.